2020
DOI: 10.1016/j.jaad.2020.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety of nine systemic medications for psoriasis: A cohort study using the Spanish Registry of Adverse Events for Biological Therapy in Dermatological Diseases (BIOBADADERM) Registry

Abstract: Background: Registry studies broadly describing the safety of systemic drugs in psoriasis are needed.Objective: To describe the safety findings of the systemic drugs acitretin, adalimumab, apremilast, cyclosporine, etanercept, infliximab, methotrexate, secukinumab, and ustekinumab used for the treatment of moderate to severe psoriasis in patients included in the Spanish Registry of Adverse Events for Biological Therapy in Dermatological Diseases (BIOBADADERM) Registry. Methods:The incidence rate ratio (IRR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 27 publications
5
42
0
3
Order By: Relevance
“…14 In a prospective safety study on the long-term safety of different medications for psoriasis, authors reported that apremilast patients had a lower risk of infections and infestations. 15 Apremilast does not affect B cells, T cells, or immunoglobulin (Ig) G and IgM secretion, but partially inhibits TNFα, interferon gamma, IL-17, and IL-23. 16 Given its immunomodulatory properties and its specific mechanism of action, 12,14,16 apremilast does not favor neither the infections nor the cytokines storm, and it will not increase the risk of pulmonary fibrosis, one of the COVID-19's mortality factors.…”
Section: Discussionmentioning
confidence: 99%
“…14 In a prospective safety study on the long-term safety of different medications for psoriasis, authors reported that apremilast patients had a lower risk of infections and infestations. 15 Apremilast does not affect B cells, T cells, or immunoglobulin (Ig) G and IgM secretion, but partially inhibits TNFα, interferon gamma, IL-17, and IL-23. 16 Given its immunomodulatory properties and its specific mechanism of action, 12,14,16 apremilast does not favor neither the infections nor the cytokines storm, and it will not increase the risk of pulmonary fibrosis, one of the COVID-19's mortality factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, acitretin also reversed Th1 and Th17 preponderance in psoriasis patients to some degree (52). But the blood lipid must be monitored during therapy with acitretin and the infection must be paid attention to when using methotrexate (6). The therapeutic effect of topical calcipotriol was achieved by attenuating the T17 cell accumulation in both treated areas and draining lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed for the specific targeting of parts of the immune system, rather than suppression of the entire immune system, leading to a favorable efficacy and safety profile (53,54). However, some studies revealed that they might cause adverse events like infection and idiopathic psoriasis (6,55). Moreover, a single drug was unable to meet the treatment of complex diseases such as psoriasis, while the combination might have an increasing risk of AEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common infectious side effects from cyclosporine were flu‐like symptoms seen in 15% of patients enrolled in an RCT for chronic idiopathic urticaria 54 . Psoriasis registries examining cyclosporine reported infection rates of 8.1–17.7 infections per 100 patient‐years 55‐57 with severe or serious infection rates of 1.4 and 2.0 per 100 patient‐years, slightly higher than comparators 56,57 . Of note, cyclosporine has been shown to inhibit the replication of diverse coronaviruses including SARS as demonstrated by in vitro experiments 58,59 …”
Section: Introductionmentioning
confidence: 99%